Molecular programs induced by heat acclimation confer neuroprotection against TBI and hypoxic insults via cross-tolerance mechanisms - Horowitz, Michal; Umschweif, Gali; Yacobi, Assaf; Shohami, Esther (Frontiers in Neuroscience, 2015)
Neuroprotection following prolonged exposure to high ambient temperatures (heat acclimation HA) develops via altered molecular programs such as cross-tolerance (Heat Acclimation -Neuroprotection Cross-Tolerance -HANCT). The mechanisms underlying cross-tolerance depend on enhanced “on-demand” protective pathways evolving during acclimation. The protection achieved is long lasting and limits the need for de novo recruitment of cytoprotective pathways upon exposure to novel stressors. Using mouse and rat acclimated phenotypes, we will focus on the impact of heat acclimation on Angiotensin II-AT2 receptors in neurogenesis and on HIF-1 as key mediators in spontaneous recovery and HANCT after traumatic brain injury (TBI). The neuroprotective consequences of heat acclimation on NMDA and AMPA receptors will be discussed using the global hypoxia model. A behavioral-molecular link will be crystallized. The differences between HANCT and consensus preconditioning will be reviewed.